2021
DOI: 10.1038/s41598-020-80589-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the frequency of electrocautery of Hunner lesions and changes in bladder capacity in patients with Hunner type interstitial cystitis

Abstract: Electrocautery is a promising treatment option for patients with Hunner type interstitial cystitis (HIC), but frequently requires multiple sessions due to recurrence of the lesions. In the present study, we assessed the relationship between the frequency of electrocautery of Hunner lesions and changes in maximum bladder capacity (MBC) at hydrodistension in a large cohort of 118 HIC patients. Three mixed-effect linear regression analyses were conducted for MBC against (1) the number of sessions; (2) the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…Moreover, HL fulguration demonstrated solid evidence of short‐term benefits, however the lack of long‐term relief usually leads to repeated procedures under general anesthesia. Although some studies have reported no decreased in bladder capacity after repeated fulgurations, 7,19 a recent retrospective study of 118 patients demonstrated a significant relationship between the number of fulgurations and maximal bladder capacity, with an approximately 50 ml decrease for each additional fulguration session 20 . We believed that the introduction of a maintenance treatement of low‐dose CyA immediately following HL fulguration could prevent symptom recurrence by sustainably decreasing the bladder inflammatory condition and therefore decreasing the frequency of fulgurations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, HL fulguration demonstrated solid evidence of short‐term benefits, however the lack of long‐term relief usually leads to repeated procedures under general anesthesia. Although some studies have reported no decreased in bladder capacity after repeated fulgurations, 7,19 a recent retrospective study of 118 patients demonstrated a significant relationship between the number of fulgurations and maximal bladder capacity, with an approximately 50 ml decrease for each additional fulguration session 20 . We believed that the introduction of a maintenance treatement of low‐dose CyA immediately following HL fulguration could prevent symptom recurrence by sustainably decreasing the bladder inflammatory condition and therefore decreasing the frequency of fulgurations.…”
Section: Discussionmentioning
confidence: 95%
“…Although some studies have reported no decreased in bladder capacity after repeated fulgurations, 7,19 a recent retrospective study of 118 patients demonstrated a significant relationship between the number of fulgurations and maximal bladder capacity, with an approximately 50 ml decrease for each additional fulguration session. 20 We believed that the introduction of a maintenance treatement of low-dose CyA immediately following HL fulguration could prevent symptom recurrence by sustainably decreasing the bladder inflammatory condition and therefore decreasing the frequency of fulgurations. To the best of our knowledge, there is no study that has evaluated the long-term efficiency and safety of HL fulguration as the sole local treatment systematically associated with daily oral CyA.…”
Section: Discussionmentioning
confidence: 99%
“…However, intractable bladder pain and associated lower urinary tract symptoms may persist even after repeated sessions of electrocautery. Some patients progressively develop contracted bladder, which frequently induces VUR and/or hydronephrosis 8 . Cystectomy may be an option for these patients with end‐stage HIC 1‐3 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular patient-reported outcome measures and self-assessment questionnaires, such as the OAB symptom score (OABSS), the 8-item overactive bladder questionnaire (OAB-v8), and Overactive Bladder-Bladder Assessment Tool (OAB-BAT) are frequently preferred in clinical trials [14,21,22]. In contrast, the diagnosis of IC is made according to American Urological Association and East Asian clinical guidelines [3,23,24]. Accordingly, cystoscopy (and histological) and/or urodynamic studies are recommended in case the diagnosis is still in doubt after a careful medical history, physical examination, and laboratory examination [24].…”
Section: Methodsmentioning
confidence: 99%
“…The underlying pathophysiological mechanism of this debilitating condition is still unclear. Recently, IC has been divided into two categories according to the presence or absence of reddish mucosal lesions with abnormal capillary structures in the bladder, which are known as Hunner lesions [3]. IC with Hunner lesions (Hunner-type IC) is regarded as a distinct immunological inflammatory disease entity characterized by urothelial erosion and lymphoplasmacytic infiltration [4].…”
Section: Introductionmentioning
confidence: 99%